Normative Inconsistency of Itsbat Nikah: Judicial Reasoning and the Monogamy Principle in Indonesian Religious Courts - Putri Pratama Rahmatia Hunowu; Nur Mohamad Kasim; Sri Nanang Meiske Kamba; Hanira Hanafi (al-Battar: Jurnal Pamungkas Hukum, 2026)
This study aims to analyze the legal position of itsbat nikah on marriages that take place when one of the parties is still bound by a valid marriage and examine how religious courts balance the principle of monogamy with the usefulness of law in judicial practice. This study fills in the gap of previous research that focused more on judges' considerations and the legal consequences of marriage itsbat, while the analysis of normative inconsistencies between marriage legalization and marriage prohibition is still limited. The research uses normative legal methods with legislative, case, and conceptual approaches. Primary legal materials are in the form of laws and regulations and the Decision of the Gorontalo Religious Court Number 311/Pdt.P/2019/PA. Gtlo, supported by secondary legal material that is analyzed qualitatively through systematic and grammatical interpretation. The results of the study show that the granting of the application for itsbat nikah in the decision is normatively contrary to the principle of monogamy and the provisions of the prohibition of marriage in Indonesian marriage law. However, judges use judicial reasoning that is oriented towards the usefulness of the law by prioritizing the protection of family legal status, the certainty of civil relations, and the interests of the parties. These findings show a conflict between legal certainty and legal expediency in the implementation of itsbat nikah. The study concluded that the practice of granting itsbat nikah to marriage carried out while still bound by a previous marriage reflects normative inconsistencies in the application of marriage law. Therefore, clearer and more consistent judicial guidelines are needed to ensure harmony between the protection of civil rights and the enforcement of the principle of monogamy in religious judicial practice.